SOSIALISASI SAMPAH PLASTIK DI SMP NEGERI 1 SEUNAGAN KABUPATEN NAGAN RAYA - Okta Rabiana Risma; Yenny Ertika; Nabila Hilmy Zhafira; Rollis Juliansyah; Affandi Affandi (Universitas Teuku Umar, 2021)
Plastic waste produced every day becomes very influential to the survival ofnot only humans, but also to animals and plant. One of the steps to protect the environment from plastic waste is to by utilizing it into something that has value added that can be profit. The resulting plastic waste can be processed into products that can be used daily or can be marketed. Plastic waste utilization situation has two positive impact that is the first is able to reduce environmental pollution and the second is able to produce products/goods that have a selling value.